Persepsi Perempuan dalam Menginterpretasi Quarter Life Crisis - Putra, Kevin Gutomo; Agustrijanto (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
Quarter life crises tend to attack women compared to men, because women have more demands and roles to do at one time. For example, getting married, raising children, working and having a career, having a good financial condition, and building a social life. One of the efforts usually made by women in overcoming the quarter life crisis is by conducting interpersonal communication with other individuals to simply pour out their hearts or even find solutions. This study focuses on women's perceptions of the quarter life crisis and how they can overcome the quarter life crisis by conducting interpersonal communication. The research method used is descriptive qualitative. The results showed that women's perceptions in overcoming the quarter life crisis phase were by doing all positive ways such as discussing and telling stories to friends or the surrounding environment, introspecting themselves, and reflecting on everything that had happened by thinking about solutions that would be done so that the problem was solved.